PENGARUH POWER SUPPLY TERHADAP KINERJA COOLER BOX MINI PADA SISTEM TERMOELEKTRIK PELTIER - Setiawan, Dibyo; Siahaan, Herbert Hasudungan; Ferdiyansyah, Ferdiyansyah; Wibowo, Cahyo; Kurniasetiawati, Annisa Syafitri (Steam Engineering, 2024)
Indonesia has tropical climate characteristics, so it requires a cooling device where the utilization can be used as a room cooler and storage. Cooling machines generally use refrigerant working fluid in the compressor, refrigerant is a gas that is not environmentally friendly. So it is necessary to conduct alternative studies, that can replace refrigerant gas and simplify dimensions, weight, and convenience. This study was conducted to analyze the effect of applying a power supply on the performance of thermoelectric coolers. The experimental method applied 2 types of power supplies for thermoelectric Peltier coolers in cooling the mini cooler box space, then the 1400 ml capacity cooling room was given a varying volume of drinks. Analysis of the effect of using a power supply on the cooling performance of the mini cooler box on the thermoelectric Peltier system obtained the results that the time to reach the ambient temperature takes different times. The greater the load put into the box, the longer it takes to cool the drinking water. The greater the power supply ampere specifications, the better it is in accelerating the cooling rate but the power required is greater such as the application of the type of power supply with the type 20A.